Design of a 13.56 MHz IPT system optimised for dynamic wireless charging environments - Arteaga,JM; Aldhaher,S; Kkelis,G; Yates,DC; Mitcheson,PD (IEEE, 2017)
Inductive power transfer (IPT) systems are often designed to achieve their highest efficiency at a fixed load value and at a fixed coil separation distance and misalignment. A variation in the position of the coils or the load value tends to drastically affect the efficiency, and therefore makes the designed IPT system not practical for applications that are mobile with variable loading conditions such as dynamic wireless charging for electric vehicles. This paper presents a novel design approach for loosely-coupled IPT systems that can inherently maintain efficient operation against changes in the system's characteristics, coil geometries and loading conditions. The transmitting-end of the proposed IPT system consists of a Load-Independent Class EF inverter that provides a constant amplitude current in the transmitting-end coil and achieves zero-voltage switching (ZVS) independent of the coupling factor and the load resistance. A Class D rectifier with a resistance compression network (RCN) was implemented for the receiving-end of the IPT system to ensure that the reflected resistance to the transmitting-end is at its optimum value with minimal dependence on the output load resistance. The combination of the features of the inverter and rectifier allow the IPT system to operate efficiently across a wide range of air gaps, without retuning. Experimental results show a maximum DC-DC efficiency of 83% with a coil separation of one coil diameter and 85 W output power. A weighted average DC-DC energy transfer efficiency (where the coils move through zero alignment, to full alignment, and back to zero alignment at constant velocity), was measured at 73%.